(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Severe hand, foot and mouth disease (HFMD) caused by Enterovirus A71 (EV-A71) may lead to acute pulmonary edema, central nervous system involvement, and cardiopulmonary failure, potentially resulting in death without timely intensive care. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) has emerged as a salvage therapy in cases unresponsive to conventional treatment. However, clinical data regarding ECMO in pediatric EV-A71-associated HFMD grade IV remain limited in Vietnam. Objectives and methods:We report the first three pediatric cases in Vietnam with EV-A71-associated HFMD grade IV treated with combined VA-ECMO and continuous renal replacement therapy (CRRT) at Children’s Hospital 2 in 2023. Results: All three patients experienced clinical deterioration on illness day 3, presenting with pulmonary edema, autonomic nervous system dysregulation, and acute heart failure. Despite early initiation of CRRT (within 2–2,5 hours of hospital admission), all developed cardiogenic shock with a reduced ejection fraction (EF 30%) and refractory ventricular arrhythmias, necessitating ECMO support. Hemodynamic and metabolic parameters significantly improved within 8–24 hours of ECMO initiation. Cardiac function nearly normalized between 36–144 hours. Brain MRI in all cases revealed brainstem involvement. All patients recovered consciousness and were discharged in good condition. Conclusion: VA-ECMO combined with CRRT may be a life-saving intervention for children with EV-A71-associated HFMD grade IV complicated by cardiopulmonary failure and refractory arrhythmias. Early initiation is key to improving outcomes and minimizing neurological sequelae.